Media Pembelajaran Digital Sebagai Sarana Pembentukan Karakter Islami pada Anak - Azizatul Maghfiroh; Amrullah Amrullah; Aulia Ridwan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
This study discusses the role of digital learning media in the formation of Islamic character in children. In the increasingly advanced digital era, the use of technology in education has provided both opportunities and challenges. Through library research methods, this study explores various digital media such as interactive multimedia, learning videos, and learning management platforms that can support the process of internalizing Islamic values. In addition to its benefits in creating flexible and engaging learning experiences, this study also reveals the risks of exposure to negative content and the impact of technology on children's social interactions. Therefore, proper supervision from educators and parents is needed in the application of digital media to achieve the goals of Islamic character education optimally.